THE ROLE OF TECHNOLOGY IN PREVENTING AND FIGHTING ORGANIZED CRIME, FINANCIAL CRIMES AND CORRUPTION.: INTELLECTUAL PROPERTY RIGHTS AND LEGAL PROTECTION, HIGH TECHNOLOGY CRIMES. - MSc, Ana Rushiti (IJRDO - Journal of Social Science and Humanities Research, 2022)
Albania is a country where very little has been said about intellectual and industrial property. The chosen topic is a necessary topic to be addressed as intellectual property is in great need of experts in this important field. Many certain individuals make works like in music, in various arts, poetry, various scientific articles, the production of a trademark in the market, but they do not know their rights and obligations arising from intellectual property. In this paper it is important treatment of the albanian legal framework versus the european legal framework related to intellectual property. The study of European Union directives and international court decisions is very important as it helps us make the necessary changes in the law by applying the principle of proportionality. It is also important in case of copyright infringement to have legal protection. Legal protection can be done with a lawyer or self-defense. Legal protection is very important as it is a principle recognized by the European Convention on Human Rights (ECHR). We live in the digital age where every service is available online, but high technology has brought many problems ranging from the physical and psychological formation of the child to the copyright infringement. This is a global issue and many websites have tried to protect the rights of copyright or inventor. Dealing with cases in a practical way would make the work more interesting, but also more practical. I have participated in conferences such as the NATO Model Conference, National and International Student Conferences and I have also conducted training in the field of legal protection of authors & inventors. In the trainings I participated in I received an important message was "Motivation is the important weapon of success".